Impact of platelet lysate on immunoregulatory characteristics of equine mesenchymal stromal cells - Moellerberndt, Julia; Niebert, Sabine; Fey, Kerstin; Hagen, Alina; Burk, Janina (Frontiers in Veterinary Science, 2024)
Multipotent mesenchymal stromal cells (MSC) play an increasing role in the treatment of immunemediated diseases and inflammatory processes. They regulate immune cells via cell-cell contacts and by secreting various anti-inflammatory molecules but are in turn influenced by many factors such as cytokines. For MSC culture, platelet lysate (PL), which contains a variety of cytokines, is a promising alternative to fetal bovine serum (FBS). We aimed to analyze if PL with its cytokines improves MSC immunoregulatory characteristics, with the perspective that PL could be useful for priming the MSC prior to therapeutic application. MSC, activated peripheral blood mononuclear cells (PBMC) and indirect co-cultures of both were cultivated in media supplemented with either PL, FBS, FBS+INF-γ or FBS+IL-10. After incubation, cytokine concentrations were measured in supernatants and control media. MSC were analyzed regarding their expression of immunoregulatory genes and PBMC regarding their proliferation and percentage of FoxP3+ cells. Cytokines, particularly IFN-γ and IL-10, remained at high levels in PL control medium without cells but decreased in cytokine-supplemented control FBS media without cells during incubation. PBMC released IFN-γ and IL-10 in various culture conditions. MSC alone only released IFN-γ and overall, cytokine levels in media were lowest when MSC were cultured alone. Stimulation of MSC either by PBMC or by PL resulted in an altered expression of immunoregulatory genes. In co-culture with PBMC, the MSC gene expression of COX2, TNFAIP6, IDO1, CXCR4 and MHC2 was upregulated and VCAM1 was downregulated. In the presence of PL, COX2, TNFAIP6, VCAM1, CXCR4 and HIF1A were upregulated. Functionally, while no consistent changes were found regarding the percentage of FoxP3+ cells, MSC decreased PBMC proliferation in all media, with the strongest effect in FBS media supplemented with IL-10 or IFN-γ. This study provides further evidence that PL supports MSC functionality, including their immunoregulatory mechanisms. The results justify to investigate functional effects of MSC cultured in PL-supplemented medium on different types of immune cells in more detail.